Effect of production system on physical–chemical, antioxidant and fatty acids composition of Longissimus dorsi and Serratus ventralis muscles from Iberian pig (Food Chemistry, 2012)
The effect of three production systems of Iberian pigs namely Montanera (free-range system and feeding based on acorns and grass), Recebo (free-range system and nutrition based in combination of acorns, grass and mixed feeds) and Intensive (conﬁnement with mixed feeds) on some quality traits of Longissimus dorsi (LD) and Serratus ventralis (SV) muscles were studied. Muscles from pigs raised in the Montanera system showed signiﬁcantly higher CIE L ⁄ , a ⁄ and b ⁄ values and higher haem pigment content than those from Intensive system. Similarly, muscles from pigs raised in the Montanera system had signiﬁcantly higher contents of a and c-tocopherol and phenolic compounds contents and higher lipophilic and hydrophilic activity antioxidant than those from pigs raised in the Intensive system. Fatty acids proﬁles from Montanera pigs had signiﬁcantly higher monounsaturated (MUFA) and polyunsaturated (PUFA) fatty acids and lower saturated fatty acids (SFA) than those from pigs raised in the Intensive system. In relation to muscle effect, LD showed lower intramuscular fat (IMF), a-tocopherol, phenolic compounds, lipid oxidation and PUFA, but higher MUFA than SV.

Study of variability in antioxidant composition and fatty acids profile of Longissimus dorsi and Serratus ventralis muscles from Iberian pigs reared in two different Montanera seasons. (Meat science, 2012)
This investigation was designed to evaluate the effects of variations in antioxidant and fatty acids composition of acorns and grass from two Montanera (free-range system and feeding based on acorns and grass) seasons (2006/07 and 2007/08) on the antioxidant composition and fatty acids profile of m. Longissimus dorsi (LD) and m. Serratus ventralis (SV) from Iberian pigs reared under these Montanera seasons. Acorn and grass composition was affected by Montanera season and consequently, LD and SV muscles showed different contents of α-tocopherol, total phenols, hydrophilic and lipophilic antioxidant activity and fatty acid profile, according with the composition of acorns and grass ingested. Results suggest a lack of uniformity in meat quality between different seasons. This could be due to the variable nature of extensive pig production as reflected in the variability in the composition of the diet (acorns and grass).

Water-holding capacity and instrumental texture properties of m. Longissimus dorsi and m. Serratus ventralis from Iberian pigs as affected by the production system (Livestock Science, 2012)
Meat from Iberian pigs had a high quality and an important acceptance for consumers, but is affected enormously by production conditions. So, in this study, ninety Iberian pigs were randomly allotted into three batches – Montanera (free-range rearing and fed on acorns and grass), Intensive (conﬁnement rearing and fed on concentrate) and Recebo (free-range rearing fed on acorn, grass and concentrate) – in order to characterize the inﬂuence of the production system on water holding capacity (WHC), drip loss, thaw loss and cook loss and instrumental texture traits of m. Longissimus dorsi and m. Serratus ventralis. Muscles from pigs raised in Montanera had greater WHC and lower water losses after thawing than those from Intensive system. Instrumental texture analysis showed that muscles from Montanera pigs had different characteristics as determined by instrumental Texture proﬁle analysis (TPA) and with most resistance to cutting of the muscle ﬁbres Warner–Bratzler (W–B). In all the cases, however, the type of muscle showed a different behaviour on water loss and rheological properties. So, these results suggest that meat quality of Iberian pig is highly inﬂuenced by the production system and type of muscle studied.